2012
DOI: 10.1080/15389588.2011.631065
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Underestimated Burden of Road Traffic Mortality in Mexico: A Comparison of Three Approaches

Abstract: Introduction: We present a novel multistep technique to estimate the actual burden of road traffic mortality in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 12 publications
(21 reference statements)
1
20
1
8
Order By: Relevance
“…This analysis is limited by the quality of data collection and reporting to the SIM national database. The accuracy of death certificate and hospital-coded death data has long been recognized as limited (Glasser 1981;Lu et al 2001), in particular with road traffic deaths (Harris 1990;Hijar et al 2012;Lapidus et al 1994). Previous studies from Brazil have shown that cause-ofdeath coding in the SIM database can be limited; when reviewing coded deaths from the southern city of Porto Alegre, Fajardo et al (2009) found that nearly 13 percent needed to be recoded by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is limited by the quality of data collection and reporting to the SIM national database. The accuracy of death certificate and hospital-coded death data has long been recognized as limited (Glasser 1981;Lu et al 2001), in particular with road traffic deaths (Harris 1990;Hijar et al 2012;Lapidus et al 1994). Previous studies from Brazil have shown that cause-ofdeath coding in the SIM database can be limited; when reviewing coded deaths from the southern city of Porto Alegre, Fajardo et al (2009) found that nearly 13 percent needed to be recoded by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…http://www.sinais.salud.gob.mx/estadis ticasportema.html, accedido el 17/May/2012). Sin embargo, estas altas cifras podrían estar subestimadas en alrededor de un 30%, si se considera el número de personas cuya causa de muerte no es bien registrada o es clasificada en códigos inespecíficos 9,10,11 .…”
Section: Epidemiología De Las Lct En Méxicounclassified
“…South Korea reports road fatalities immediately after a traffic incident or within 30 days as a result of an incident, whereas Chile informs deaths that occur immediately after an incident and up to 24 hours afterwards, resulting in estimated underreporting of 500 fatalities annually (CONASET 2012). Similar to Mexico's reported underestimation of road traffic mortalities (Hijar et al 2012), Chile also likely undercounts traffic-related deaths and injuries due to inconsistencies between police and hospital records. To represent land use characteristics in the zones of analysis in Santiago, we use data from the National Statistics Institute (INE), and a spatial dataset from the Chilean police.…”
Section: Data Sourcesmentioning
confidence: 87%